ANALYSIS OF POTENTIAL CO2 LEAKAGE ZONE BASED ON TEMPERATURE PROFILE AT WELL X FROM TEMPERATURE LOG DATA - Sastra Samudra, Richi
Global warming is one of the main problems facing the world. CO2 gas emissions generated from oil and gas operations are one of the main contributors to the effects of global warming. Carbon Capture Storage (CCS)or Carbon Capture Utilization Storage (CCUS) is the answer to the problem. CCS/CCUS is one of the most effective methods to reduce the impact of CO2 by injecting CO2 into injection wells for storage. However, the injection of CO2 has the risk of leakage and can compromise the integrity of the well that is converted to an injection well and the leakage can even have an adverse impact on the environment. The study focuses on analyzing the temperature profile data before and after re-cementing each depth interval at well X. The analysis includes evaluating the temperature profile at each depth interval, analyzing the movement activity of the temperature profile against the temperature gradient, and analyzing the relationship of the temperature profile movement activity to the potential CO2 leakage zone at each depth interval. This study concludes that the analysis of temperature log data results shows that there are potential CO2 leakage zones at depth intervals of 438-442 m, 520-580 m and 880-882 m. The leakage is thought to be caused by the quality of the cement. The leakage is thought to be caused by low cement quality. However, evaluation using other methods is needed to further validate the source of the CO2 leakage problem as well as the flow rate of the CO2 leakage occurring at well X.